Nanostructures based on protein self-assembly: From hierarchical construction to bioinspired materials. (June 2017) - Sun, Hongcheng; Luo, Quan; Hou, Chunxi; Liu, Junqiu
Graphical abstract: Highlights: The strategies for constructing self-assembled proteins architectures. Developing bioinspired materials based on protein assemblies. Protein assemblies based artificial light harvesting systems, intelligent protein nanocarriers, and biomimetic systems. Abstract: Sophisticated protein self-assemblies have attracted great scientific interests in recent few decades due to their various potential applications in substance/signal transmission, biosensors, or disease diagnosis and treatment. The design and construction of proteins into hierarchical nanostructures via self-assembly strategies offer unique advantages in understanding the mechanism of naturally occurring protein assemblies and/or creating various functional biomaterials with advanced properties. This review covers the recent progress and trends in the self-assembled hierarchical protein structures and their bio-inspired applications. We initially discuss the design and development of sophisticated protein nanostructures through the preciously designed protein–protein interactions. Many intricate protein nanostructures from quasi-zero dimensional (0D) polyhedral cages, one-dimensional (1D) strings/rings/tubules, two-dimensional (2D) crystal sheets/cambered surfaces, and three-dimensional (3D) crystalline frameworks/hydrogels, have been constructed through self-assembly of rationally designed proteins. In addition, we also show the representative achievements in the study of the structure–function relationship for selected protein self-assemblies and highlight the latest research progress in developing artificial light harvesting systems, biological nanoenzyme mimics, intelligent protein nanocarriers, biomimetic protocells, and so on. As expected, protein self-assembly has become a powerful tool for development of multifarious bioinspired materials with advanced structures and properties.